Pengaruh Mental Accounting dan Present Bias terhadap Perilaku Pengeluaran Konsumtif pada Mahasiswa dengan Pendapatan Rutin - Ni Kadek Denia Astari Putri; Komang Widhya Sedana Putra P (Jurnal Manajemen Riset Inovasi, 2026)
This study aims to determine the partial and simultaneous effects of mental accounting and present bias on consumptive spending behavior among students with regular income in Denpasar City. The population in this study consisted of all university students in Denpasar City who have regular income from allowances, scholarships, or part-time jobs to fulfill their daily needs and consumption. The analysis process was carried out using a quantitative approach to the collected data. The sampling technique used in this study was purposive sampling. The sample size was determined by multiplying the number of indicators by 10 (15 × 10), resulting in 150 respondents. The collected data were processed using SPSS 27.0 software. The data analysis techniques used were validity and reliability tests, classical assumption tests, multiple linear regression analysis, coefficient of determination test, t-test, and F-test. The results of the study indicate that mental accounting has a positive and significant effect on consumptive spending behavior among students in Denpasar City. Present bias also has a positive and significant effect on consumptive spending behavior among students in Denpasar City. Simultaneously, mental accounting and present bias have a positive and significant effect on consumptive spending behavior among students in Denpasar City. Therefore, students are advised to be more rational in making financial decisions by considering needs and long-term benefits and avoiding spending solely for social recognition.